Digital Innovations Supporting Women Agri-entrepreneurs in India: Mapping Good Practices - Dominic, D.M.; Bhuvana, N.; Mittal, N.; Sulaiman, R.V.; Puskur, Ranjitha (Centre for Research on Innovation and Science Policy, 2024)
Agribusiness startups are currently redefining the Indian agricultural sector, encouraging a more entrepreneurial mindset among the various stakeholders. This surge of interest coupled with advancements in the digital sector has led to a rapid expansion in the technology and digital solutions ecosystem within the sector. The process of creating a new enterprise is being greatly aided by technologies such as big data, Artificial Intelligence (AI), Internet of Things (IoT), and various digital platforms. These technologies are currently helping them with everything from conceptualization of ideas to recognition of opportunities for production, marketing, and distribution. The proliferation of digital technologies is offering unprecedented opportunities for women to participate in, and lead, agricultural enterprises in India by helping them overcome the many longstanding barriers they once faced, including limited access to information, resources, and markets. However, despite these positive developments, challe